PEMBUKTIAN AUTOMORFISMA PADA GELANGGANG POLINOM MIRING UNTUK PEMBENTUKAN GELANGGANG POLINOM MIRING BERSUSUN - Amir Kamal Amir (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
Let R be any ring with identity 1, ????1 be an endomorphism of R and ???? derivation. The skew polynomial ring over R in an indeterminate ???? 1, denoted by ????[????], is the set of polynomials ???????? ????1 ???? + ???? ???? −1 ???? 1 ???? −1 + ⋯ + ???? 0 where ???? ∈ ???? with multiplication rule ???? 1 ???? = ???? 1 ???? ???? 1 + ????1 ???? (????) for all ???? ∈ ????. In this paper, it will be proved an automorphism ???? on the skew polynomial ring ????[???? 1 ; ???? 1 , ???? ], such that with that automorphism we can construct a iterated skew polynomial ring with variabel ????1 and ????2, i.e., ????[????1;????1;????1][????2;????2].